Analisis Narrative Criticism Kisah Simson dan Ironi Kehidupannya di Dalam Kitab Hakim-Hakim - Sonny Eli Zaluchu (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2020)
The story of Samson as Israel's last judge becomes the primary material in the narrative criticism approach as an analytical tool. This story is chosen because it is a complete story and contains many conflicts and irony. The author-speech intent of the story will be examined in the interest of today's readers. The narrative analysis method that the author uses is the background story (background); location and time (setting of time and location); storyline (plot); events and their causes (causal links); character identification; conflicts that have occurred (conflicts); tragic things (irony); relationship with other texts (intertextuality); and main emphasis (point of view). The results show that the story of Samson does not stop at the readers who are the target of the story in the past. Samson's life as a nazir becomes a reflection and an example for today's readers about the importance of respecting, maintaining, and completing every task and call of God in ​​life where God places everyone. Kisah Simson sebagai hakim terakhir Israel menjadi materi primer di dalam pendekatan kritik naratif sebagai alat analisis. Kisah ini dipilih karena merupakan sebuah cerita (stories) yang lengkap dan utuh dan mengandung banyak konflik serta ironi. Maksud penulis-tutur dari kisah tersebut akan diteliti dalam kepentingan pembaca masa kini. Metode analisis naratif yang penulis gunakan adalah latar belakang kisah (background); lokasi dan waktu (setting of time and location); alur cerita (plot); peristiwa-peristiwa dan penyebabnya (causal links); identifikasi karakter melalui tokoh (character identification); konflik-konflik yang terjadi (conflicts); hal-hal tragis (irony); hubungannya dengan teks lain (intertextuality); dan penekanan utama (point of view). Hasil yang diperoleh dari analisis ini memperlihatkan cerita tentang Simson tidak berhenti hanya pada pembaca yang menjadi tujuan kisah di masa lalu. Kehidupan Simson sebagai nazir menjadi refleksi dan teladan bagi pembaca masa kini mengenai pentingnya menghormati, menjaga dan menuntaskan setiap tugas dan panggilan Tuhan di dalam bidang kehidupan dimana Tuhan menempatkan setiap orang.